2020
DOI: 10.1016/j.ymssp.2019.106580
|View full text |Cite
|
Sign up to set email alerts
|

On the application of Gaussian process latent force models for joint input-state-parameter estimation: With a view to Bayesian operational identification

Abstract: The problem of identifying dynamic structural systems is of key interest to modern engineering practice and is often a first step in an analysis chain, such as validation of computer models or structural health monitoring. While this topic has been well covered for tests conducted in a laboratory setting, identification of full-scale structures in place remains challenging. Additionally, during in service assessment, it is often not possible to measure the loading that a given structure is subjected to; this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…A major goal of this paper is to design an SHM approach robust to the unknown input S g k without assuming or estimating its statistical properties. This study thus neither reconstructs the unknown input S g k as in [12,26,27,29,38], nor estimates its statistics as in [15,34].…”
Section: Unknown Input Rejection From System Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A major goal of this paper is to design an SHM approach robust to the unknown input S g k without assuming or estimating its statistical properties. This study thus neither reconstructs the unknown input S g k as in [12,26,27,29,38], nor estimates its statistics as in [15,34].…”
Section: Unknown Input Rejection From System Dynamicsmentioning
confidence: 99%
“…With a similar objective, [12] proposed a dual filtering approach in which the structural parameters, as augmented states, are jointly estimated with the response states conditioned on an estimate for the input force. Instead of an explicit reconstruction of the input forces, [34] estimated the input force model through the parameters of a Gaussian process within a Bayesian framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most useful aspects of this approach is that the whole system remains a linear Gaussian state-space model which can be solved with the Kalman filter and RTS smoother to recover the filtering and smoothing distributions exactly. It is this form of the model that has been exploited previously in structural dynamics [5,6,10].…”
Section: Input Estimation As a Latent Force Problemmentioning
confidence: 99%
“…Ding et al [9] present an approach based on an unscented Kalman filter. In recent work, Rogers et al [10] showed how the Gaussian process latent force framework could be used to solve this problem in a Bayesian manner with minimal user input.…”
Section: Introductionmentioning
confidence: 99%